Historical perspectives on sustainable fashion : inspiration for change - Holroyd, Amy Twigger; Farley Gordon, Jennifer; Hill, Colleen, 1982- (Bloomsbury Visual Arts, 2023)
"Historical Perspectives on Sustainable Fashion in Fashion reminds us that concerns about workers' rights and chemical pollution in the fashion industry have been with us as far back as the early 19th century. By placing today's sustainable fashion movement in its historical context, this book encourages contemporary designers to learn from past failures and build on their predecessors' successes to move the business of fashion forward. As well as new international examples from each stage of the fashion production cycle, this revised edition includes a new opening chapter outlining the different fashion systems and their role in sustainable practice. There's also a new chapter on how the consumer can play a role in the environmental impact of their clothing, exploring the importance of emotional significance and value, shopping and e-commerce as well as laundering and care"
Keywords: oděvnictví -- environmentální aspekty; módní návrhářství; móda -- environmentální aspekty; udržitelná spotřeba a výroba; clothing trade -- environmental aspects; fashion design; fashion -- environmental aspects; sustainable consumption and production; elektronické knihy; monografie; electronic books; monographs